2012
DOI: 10.1007/s00405-012-2095-3
|View full text |Cite
|
Sign up to set email alerts
|

Improved quality of life in adults undergoing tonsillectomy for recurrent tonsillitis. Is adult tonsillectomy really a low priority treatment?

Abstract: There is a paucity of studies on patient-reported outcome measures in adult tonsillectomy. Our aim was to add to the body of health-related quality of life (HRQOL) evidence on adult tonsillectomy at a time when this intervention is being branded a low priority treatment in the United Kingdom (UK). We designed a prospective questionnaire study that was carried out in two UK district general hospitals. 41 patients were recruited into the study and completed a pre-operative short form 36 questionnaire. All 41 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…This high effectiveness of tonsillectomy in chronic and recurrent tonsillitis in adults is in line with several previous publications . The effects are likely to be long‐lasting and have a greater impact on younger patients …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This high effectiveness of tonsillectomy in chronic and recurrent tonsillitis in adults is in line with several previous publications . The effects are likely to be long‐lasting and have a greater impact on younger patients …”
Section: Discussionsupporting
confidence: 89%
“…The role of tonsillectomy in adolescents and adults with chronic or recurrent tonsillitis is less well investigated. Recent reports suggest improved quality of life following tonsillectomy . The standard surgical procedure in chronic or recurrent tonsillitis traditionally has been extracapsular tonsillectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Tonsillectomy is among the most common surgical procedures in otolaryngology and is often performed for recurrent tonsillitis . While a few observational studies report that patients with chronic or recurrent tonsillitis have improved QoL after tonsillectomy, these reports have been primarily retrospective with rather low response rates implying a high risk of substantial information bias and selection bias . Moreover, both the distribution of the QoL change and whether and to what extent this change can be predicted by any preoperative anamnestic or clinical findings have been poorly reported.…”
mentioning
confidence: 99%
“…In contrast to this statement a more recent study concluded, that the quality of life significantly improved after TE [86]. Comparable studies are currently undertaken in the UK as an answer to the restrictions of the National Health System (NHS) [87]. The NHS has stated for TE cases, that a reimbursement can be expected only for malignancy, a second event of a peritonsillar abscess or acute upper airway obstruction.…”
Section: Discussionmentioning
confidence: 99%